Inorganic and organic hybrid solid electrolytes for lithium-ion batteries. Issue 23 (6th April 2016) - Fu, Xiaotao; Yu, Danni; Zhou, Junwen; Li, Siwu; Gao, Xing; Han, Yuzhen; Qi, Pengfei; Feng, Xiao; Wang, Bo
Abstract : Two inorganic–organic hybrid solid electrolyte systems for lithium-ion batteries are described: polymer electrolytes with inorganic fillers and metal–organic framework-based solid electrolytes. Abstract : Lithium ion batteries (LIBs) have achieved great success in powering portable electronic devices in our modern society, and are to find use in the electrification of transportation and the storage of wind or solar energy in smart grids in the near future. However, there is increasing concern on the safety issues of current LIBs based on organic liquid electrolytes, which are volatile and flammable. This leads to the exploration and development of solid electrolytes to improve the safety of next-generation high-energy LIBs. In this review, we describe two inorganic–organic hybrid solid electrolyte systems for LIBs. Firstly, we present polymer electrolytes with different types of inorganic fillers, discussing how the fillers affect the electrochemical and physical properties of the electrolyte. Secondly, we introduce recent progress in MOF-based solid electrolytes and show how MOFs can contribute to such an inorganic–organic hybrid system. Finally, outlook and future directions for safe and high performance inorganic–organic hybrid solid electrolytes are proposed.